SWOT Analysis of The Application of Financial Technology in Mobile Services PT. Bank Syariah Indonesia - Alfadri, Ferri; Surya, Eko (Journal of Islamic Financial Technology, 2023)
This research is motivated by problems experienced by BSI Mobile service users. BSI Mobile's frequent request time out errors cause transactions to be hampered, causing inconvenience for customers. This research aims to determine the SWOT Analysis of the Application of Financial Technology in Mobile Banking Services at PT Bank Syariah Indonesia KC Padangsidimpuan. This research was analyzed qualitatively descriptively using the SWOT matrix, IFAS (Internal Factor Analysis Summary) matrix and EFAS (External Factor Analysis Summary) matrix.The research results show that the SWOT Analysis of the Application of Financial Technology in Mobile Banking Services at PT. Bank Syariah Indonesia KC. Padangsidimpuan obtained the coordinate point (1.34 : 1.16). So the position of mobile banking services at PT. Bank Syariah Indonesia KC Padangsidimpuan is in Quadrant 1. This is a profitable situation because it can maximize strengths and take advantage of existing opportunities.